(untitled) (TEST Ticontre. Theory Text Translation, 2018)
Starting from the meaning of melancholy and some famous examples of poetic melancholy (Novalis, Keats, Baudelaire), the essay reconsiders the relationship between Pascoli and the umor melancolicus. Pascoli’s melancholy is analyzed from a historical point of view (the controversial relationship with the sisters Ida and Maria, especially with the first; the failed attempts at marriage), from a poetic perspective (women of myth and of the past: Circe, Nausicaa, Sappho); and in a third sense that summarizes and exceeds the historical-biographical and purely narrative path: the symbolic and metapoetic interpretation. In most cases, Pascoli’s woman is an enigmatic, elusive entity: the poet wish to join with her, but this hope is always disappointed. In the light of the models and of the cultural/epistemological revolution in which Pascoli’s lyric has grown, in our opinion Pascoli’s melancholy is a mirror or idealization of the ménage between the author and poetry in its essence of energy capable of instantly erasing the barriers between reality and other worlds: opening and immediately closing a channel of exchange with times, ideals and loved ones at Pascoli and now inexorably vanished.